Vulnerability, complexity and risk management in global livestock supply chains: The case of the MV Bahijah - Jackson, Elizabeth (John Wiley & Sons, 2025)
New to this Edition: Expanded discussion of sustainability and ethical supply chain practices In-depth analysis of supply chain vulnerability and risk management Greater emphasis on reverse logistics and circular economy strategies Enhanced ...